Understanding variations of thermal hysteresis in barocaloric plastic crystal neopentyl glycol using correlative microscopy and calorimetry - Rendell-Bhatti, Frederic; Boldrin, David; Dilshad, Melony; Moya, Xavier; MacLaren, Donald A (IOP Publishing, 2024)
Plastic crystals (PCs) exhibit solid–solid order-disorder first-order phase transitions that are accompanied by large correlated thermal and volume changes. These characteristics make PCs promising barocaloric solid-state working bodies for heating and cooling applications. However, understanding the variation of transition temperatures and thermal hysteresis in PCs with cycling is critical if these materials are to replace traditional gaseous refrigerants. Here, for the archetypal barocaloric PC neopentyl glycol (NPG), we correlate microstructure obtained from scanning electron microscopy with local and total thermal changes at the phase transition from infra-red imaging and calorimetry, respectively. We outline an evolution in microstructure as NPG recrystallises during repeated thermal cycling through its solid–solid phase transition. The observed microstructural changes are correlated with spatially inhomogeneous heat transfer, yielding direct insight into the kinetics of the phase transition. Our results suggest that the interplay of these processes affects the undesirable thermal hysteresis and the nature of the kinetic steady-state microstructures that are stabilised during cycling between the ordered and disordered phases. These observations have implications for using NPG and other PCs as technologically relevant barocaloric materials and suggest ways in which the hysteresis in these types of materials may be modified.
Keywords: 40 Engineering; 4016 Materials Engineering